PENYULUHAN HUKUM TENTANG BAHAYA NARKOBA BERDASARKAN UNDANG-UNDANG NO. 35 TAHUN 2009 DI KELURAHAN MARGA MULYA RW 08 - Muhammad Rifqy Dwi Saputra; Novita Sari; Susilo Wira Puspita Sari; Alvin Yanuar Handritartha; Gojin Gojali; Oscar Aditya Darmawan; Teuku Radja Iqbal Adamy; Yudha Prasetyo (Abdi Bhara, 2023)
Drug abuse is currently a serious concern, involvingvarious groups of society such as students, students, teachers,lecturers, TNI/POLRI, DPR, and even state officials. IndonesianPresident Joko Widodo even called this situation a "DrugEmergency Status." This crime can be categorized as anextraordinary crime. Especially among students and universitystudents, drug abuse is very concerning because they are the nextgeneration of the nation. To prevent this, counseling was held tothe community at RW 08 located in Marga Mulya, North Bekasi.This service activity offers solutions in the form of seminars andeducation on drug-related concepts and rules, as well as anunderstanding of the dangers of drug abuse and early preventionefforts especially among adolescents.